Futurists and their schools: A response to Ziauddin Sardar's ‘the namesake’ - Samet, Robert H. (Futures : the journal of policy, planning and futures studies, 2010)
A ‘futurist’ is the generic term for someone seriously engaged in the consideration of future conditions. ‘Futures research’ has a systems science orientation with a planning horizon in excess of 10 years. ‘Futures studies’ has a social science connotation and ‘foresight’ is the most popular term within the management science and corporate sectors. Five schools of futures researchers are defined: 1. Environmental and geosciences. 2. Infrastructure systems and engineering technology. 3. Social, political and economic science. 4. Human life, mind and information science. 5. Business and management science. The academic route to a futures qualification is outlined with a list of futures orientated organisations. The inclusion of urbanisation in the next generation of scenarios for climate change research and assessment, would involve replacing the notion of economic equilibrium by the concept of far-from-equilibrium stability. Finally futures research is described as an evolutionary science, which will possibly become integrated within complexity science by 2050.